Evaluation of the disposal of firewood of ilex pruning (Quercus ilex) in Andalusia and its characterization for the manufacture of wood cellulose pulp. - Gutierrez, J A; Alcaide, L J; Carmona, J A; Blanco, M J D; Ot, I P; Baldovin, F L (AFINIDAD, 2002)
In this work, it is analyzed the production of firewood of the ilex pruning in Andalusia, its real disposa and future forecast. Chemical characteristics are studied, in comparison with otherr wood species: Pine (Pinus pinaster) and Eucalyptus (Eucalyptus globulus), in order to obtain wood cellulosic pulp for paper. The average firewood production of the ilex pruning corresponding to 1975-78 in Andalusia was of 78.000 T/year, with a practically uniform trend. A statistical analysis with ARMA pattern let us estimate a yearly averge production of ilex pruning firewood around 72.500 T/year for the 1999-2006 period, which could have an upward correction if the exploitation in all hoamoak woods was total. For the manufacture of cellulosic pulp from ilex pruning wood, it would be necessary to separte the cortex due to a lower content of holocellulose and alpha-cellulose and a higher content of soluble substances and lignin. The content of lignin of ilex pruning wood is lower than the one of other wood species like Pinus Pinaster (76,7%), Eucalyptus globulus (56,4%) and olive grove pruning (8%).
Keywords: Firewood; forest residues; ilex; Quercus; Wood